Upaya Peningkatan Penjualan Pada Kelompok Usaha Batu Bata Di Kelurahan Limbung, Kecamatan Bajeng, Kabupaten Gowa - Haeruddin, M. Ikhwan Maulana Haeruddin; Haeruddin, Muhammad Ilham Wardhana Haeruddin; Aslam, Annisa Paramaswary; Mustafa, Muh. Yushar (Jurusan Teknik Informatika dan Komputer, 2023)
This activity aims to provide counseling and training on entrepreneurship and marketing related to the sale of brick products. The target participants of this activity were brick-producing residents in Limbung Village, Gowa Regency. In general, participants can be expected to be very enthusiastic about following the provision of material as shown by their diligence and discipline in following each stage in the activity. Each participant was able to produce good quality brick products and was also able to market these products through both offline and online sales mechanisms. Through this activity, each participant feels the benefits of this activity and hopes that activities like this can be provided regularly and also bring new treasures to their knowledge and skills so that it will improve the standard of living of residents economically.